2022
DOI: 10.1155/2022/7319988
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Heat Transfer Analysis for MHD Flow of C u / A g -Water-Based Nanofluid on a Heated 3D Plate with Nonlinear Radiation

Abstract: This paper scrutinizes the consequences of radiation and heat consumption of MHD convective flow of nanofluid on a heated stretchy plate with injection/suction and convective heating/cooling conditions. The nanofluid encompasses with C u and A g nanoparticles. We enforce the suited transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Tey reported that the NFT reduces when enriching the SI parameter. Eswaramoorthi et al [26] reviewed the signifcance of the MHD fow of Cu/Ag-water-based NF past a 3D plate with SI. Tey noticed that the SI parameter develops the HTG.…”
Section: Introductionmentioning
confidence: 99%
“…Tey reported that the NFT reduces when enriching the SI parameter. Eswaramoorthi et al [26] reviewed the signifcance of the MHD fow of Cu/Ag-water-based NF past a 3D plate with SI. Tey noticed that the SI parameter develops the HTG.…”
Section: Introductionmentioning
confidence: 99%
“…Saleh and Sundar (2021) focus on exergy and entropy transportation in hybridized nanofluids containing nano-diamonds in a circular tube. Recently, Eswaramoorthi et al . (2022) investigate thermal and entropy transport in hydromagnetic water-driven nanofluids over a bidirectional stretching device with the incorporation of radiation phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Solar reflectance greater than 95% requires a thickness of 160 m. Sweat wicking and drying are hindered. A major personal thermoregulation pathway, moisture management, in hot, humid, and sunny conditions, is essential to wick sweat away from skin and evaporate it quickly so that heat can be dissipated, and the body can cool safely [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%